2022
DOI: 10.32604/iasc.2022.024610
|View full text |Cite
|
Sign up to set email alerts
|

Electricity Theft Detection and Localization in Smart Grids for Industry 4.0

Abstract: Industry 4.0 is considered as the fourth revolution in industrial sector that represents the digitization of production process in a smarter way. Industry 4.0 refers to the intelligent networking of machines, their processes, and infrastructure, as well as the use of information and computer technology to transform industry. The technologies like industrial internet of things (IIoT), big data analytics, cloud computing, augmented reality and cyber security are the main pillars of industry 4.0. Industry 4.0, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…However, few works have been found that balance the data distribution. G. 4 Only one study [32] applied a deep learning model but without any feature selection or data sampling techniques. Moreover, this system classified only 6 classes.…”
Section: Cic-ids2017 Related Workmentioning
confidence: 99%
“…However, few works have been found that balance the data distribution. G. 4 Only one study [32] applied a deep learning model but without any feature selection or data sampling techniques. Moreover, this system classified only 6 classes.…”
Section: Cic-ids2017 Related Workmentioning
confidence: 99%
“…In addition, the precise location of theft is displayed on the webpage using the geolocation application programming interface (API) on Google Maps. The proposed system can be easily integrated into the smart grid network structure, helping enterprises increase their business [5].…”
Section: Introductionmentioning
confidence: 99%